STANDAR PELAYANAN PENCATATAN PERKAWINAN DI KOTA PEKANBARU - Joanne Alma CH; Dadang Mashur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
background backs of the study of marriage registration services in the city of Pekanbaru given by the Department of Population and Civil Registry and the Office of Religious Affairs has not gone well. Requirements given and the procedures to go through so much and obscurity costs make the community (especially with the economy of middle) becomes unwilling to registry their registration of marriages. The purpose of this study was to determine the Marriage Registration Service Standards in Pekanbaru and determine the factors that affect the Marriage Registration Service Standards.The concept of theory used by author is the concept of public services by Widodo. Author uses qualitative researches with descriptive study. In collecting data author uses the technique of interviewing and observation. Author uses the technique purposive sampling and accidental sampling to determine informants as the sources of information.From the analysis of qualitative descriptive data services carried out by the Department of Population and Civil Registration in Pekanbaru and Office of Religious Affairs of Pekanbaru City in the service of registration of marriages categorized not meet minimum service standards. This can be seen from the procedures, time of completion, and cost of service, product services, facilities and infrastructure, and the competence of personnel service providers who do not run with the maximum from the beginning until the time of completion of registration of marriages. It also found the factors that influence the Marriage Registration Service Standards in the city of Pekanbaru, namely the lack of socialization and response officers of which is still not goodKeyword : Services, Marriages Registration